2003
DOI: 10.1108/09653560310463838
|View full text |Cite
|
Sign up to set email alerts
|

Community participation and public awareness in disaster mitigation

Abstract: Describes how the Society for National Integration through Rural Development in India involves the local communities when developing disaster mitigation measures. Shows how participation of the community in resource identification, capabilities, coping mechanisms and vulnerability assessment will be more effective in the planning of a sensible and practical system, more suitable for the needs of the community. Covers contingency planning, community preparedness, task forces (comprising active youths in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 0 publications
3
54
0
4
Order By: Relevance
“…The empowerment of communities is usually utilised to identify their own needs, which is called "community-based" approaches (Wiek et al, 2010). Newport and Jawahar (2003) and Metri (2006) reported that community participation in the pre-disaster phase should include: engaging community voluntary work, meeting and awareness programs strengthen the Non-Governmental Organisations (NGOs) and community structures, coordination effective management with operational planning, participating in risk assessment and information flow by early warning system. Sadiqi et al (2015) stated that lack of community involvement often leads to poor project planning, decreased community support and an unsustainable completed project.…”
Section: Comunity Participation In Disaster Managementmentioning
confidence: 99%
“…The empowerment of communities is usually utilised to identify their own needs, which is called "community-based" approaches (Wiek et al, 2010). Newport and Jawahar (2003) and Metri (2006) reported that community participation in the pre-disaster phase should include: engaging community voluntary work, meeting and awareness programs strengthen the Non-Governmental Organisations (NGOs) and community structures, coordination effective management with operational planning, participating in risk assessment and information flow by early warning system. Sadiqi et al (2015) stated that lack of community involvement often leads to poor project planning, decreased community support and an unsustainable completed project.…”
Section: Comunity Participation In Disaster Managementmentioning
confidence: 99%
“…Vulnerable community needs to be aware of the potential threats and consequences that it has to endure in the near future. The concept of awareness has to be generated at local level (Newport & Jawahar, 2003), so that people can be prepared. In the context of disaster management, the role of the authorities is to implement disaster reduction programmes, but decision making should include the affected community.…”
Section: Community Perception and Disaster Awarenessmentioning
confidence: 99%
“…According to Pearce (2003), the community members have the right to know and understand the hazard they should be expecting so they can plan for themselves and make informed choices thus reducing their vulnerability. The community involvement elates rural appraisal in the preparation of contingency plan that would fortify the community in response during disaster (Newport & Jawahar, 2003). The preparation of community for disaster can include various things such as their knowledge on which route to take during disaster occurrences, the prioritized action during time of distress, the preparation before disaster hits and what to expect.…”
Section: Community Perception and Disaster Awarenessmentioning
confidence: 99%
“…People rely on multiple sources of information to learn about the communities they live in [28], either for the purpose of community awareness or participation [26]. Hyperlocal information is comprised of the news, people, and events that are set within a particular locality, and is of particular interest primarily to the residents of that locality [9].…”
Section: Introductionmentioning
confidence: 99%